2012
DOI: 10.1029/2011gm001088
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Value and Record Statistics in Heavy-Tailed Processes With Long-Range Memory

Abstract: Abstract. Extreme events are an important theme in various areas of science because of their typically devastating effects on society and their scientific complexities. The latter is particularly true if the underlying dynamics does not lead to independent extreme events as often observed in natural systems. Here, we focus on this case and consider stationary stochastic processes that are characterized by long-range memory and heavytailed distributions, often called fractional Lévy noise. While the size distri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…The best relevant data we have at hand is the solar flare statistics from the last 40 years, while geological tracers (nitrate concentrations in polar ice cores or select radionuclides) extend over millenia, but are not reliable proxy records of solar flares or SEP events (Schrijver et al 2012), because nitrate spikes in ice cores can also be caused by biomass burning plumes (Wolff et al 2012). Theoretical studies focus on extreme value and record statistics in heavy-tailed processes with long-range memory (Schumann et al 2012). The inclusion of memory and persistence is obviously very important, because the predicted number of extreme events during a clustered time interval can be much larger than predicted in a purely stochastic SOC model, such as in the original BTW model (Strugarek and Charbonneau 2014).…”
Section: Solar-terrestrial Effectsmentioning
confidence: 99%
“…The best relevant data we have at hand is the solar flare statistics from the last 40 years, while geological tracers (nitrate concentrations in polar ice cores or select radionuclides) extend over millenia, but are not reliable proxy records of solar flares or SEP events (Schrijver et al 2012), because nitrate spikes in ice cores can also be caused by biomass burning plumes (Wolff et al 2012). Theoretical studies focus on extreme value and record statistics in heavy-tailed processes with long-range memory (Schumann et al 2012). The inclusion of memory and persistence is obviously very important, because the predicted number of extreme events during a clustered time interval can be much larger than predicted in a purely stochastic SOC model, such as in the original BTW model (Strugarek and Charbonneau 2014).…”
Section: Solar-terrestrial Effectsmentioning
confidence: 99%
“…[31] In particular, such behavior is expected based on the Omori-Utsu law and the productivity law, which in the context of the ETAS model fully determine the average time interval between a main shock and its last aftershock: From extreme value statistics it follows that the average duration of a directly triggered aftershock sequence scales asymptotically as 10 (˛/p)m [Schumann et al, 2012]. Figure 11 shows that our method to define aftershocks allows us to roughly recover such a scaling for the ETAS model.…”
Section: Duration Of Aftershock Sequencesmentioning
confidence: 99%
“…Moloney and Davidsen [] found that the block maxima of the ε parameter follow the Fréchet distribution; however, this fit overestimated the highest values. Since the Fréchet class is the limiting distribution for a variable that has a PDF with a power law tail [ Schumann et al , ], a Fréchet fit to block maxima of the ε parameter would support Burlaga's earlier proposal of a lognormal PDF with a Pareto tail. Burlaga and Lazarus [] also found evidence for lognormal distributions of the solar wind speed, density, and temperature, and that these distributions vary with the phase of the cycle.…”
Section: Introductionmentioning
confidence: 97%